قياس مرونات الطلب العالمي على الصادرات الليبية من النفط الخام: دراســة تحليليــة قيـاسيـة للفتـرة (1970 – 2018) - هويدي الزروق احمد; نجم أسامة صالح (Scientific Journal of University of Benghazi, 2022)
The main objective of this study is to analyze the short and long-term elasticity of demand for crude oil exports in Libya during the period from 1970 to 2018. Although many previous studies used different econometric techniques, this study employed the autoregressive distributed lag (ARDL), developed by Pesaran, Shin and Smith (2001). This study is expected to present the short and long-term effects of price and income elasticity, which can be used to find out whether the change in demand for exports of crude oil is caused by a change in price or income or both. The results confirmed that income elasticity had a significant impact on the demand for crude oil exports, while price elasticity was very low. Our contribution in this study is the first attempt to estimate the long- and short-run effects of income and prices on demand for crude oil exports in Libya using a cointegration approach. Not only will this be beneficial to policymakers in Libya, but it will also contribute valuable knowledge to the existing literature on emerging economies.